Approach to the Pretransplant Evaluation of the Living Kidney Donor - Mala Sachdeva; Madhu Bhaskaran; Ernesto P. Molmenti; Donna Dalton; Joseph Mattana (Journal of Transplantation)
Evaluation of the potential kidney donor is a complex activity that differs substantially from other types of preoperative assessments. The well being of the donor, who derives no medical benefit from this surgery, must be assured in both the short term and long term, and the potential adverse consequences to the recipient must be determined as well. The criteria that must be met for a person to donate a kidney are rigorous and include medical, social, psychosocial, ethical, and legal issues. Donor evaluation can be divided into assessments to protect the health and safety of the donor and assessments to protect the health and safety of the recipient. This article provides an approach to evaluating a donor, focusing on the complex issues that an evaluator is faced with. A careful assessment of risks and benefits to both the donor and recipient can lead to favorable outcomes.